Trends and Frontiers of Research on Cancer Gene Therapy From 2016 to 2020: A Bibliometric Analysis - Hu, Shoushan; Alimire, Alifu; Lai, Yancheng; Hu, Haonan; Chen, Zhuo; Li, Yi (Frontiers in Medicine, 2021)
Background: With rapid development in molecular biology techniques and a greater understanding of cancer pathogenesis, the growing attention has been concentrated on cancer gene therapy, with numerous articles on this topic published in recent five years. However, there is lacking a bibliometric analysis of research on cancer gene therapy. Therefore, the aim of the present study was to conduct a bibliometric analysis to provide the trends and frontiers of research on cancer gene therapy during 2016-2020. Methods: We utilized CiteSpace 5.7.R5 software to conduct a bibliometric analysis of publications on cancer gene therapy published during 2016-2020. The bibliometric records were obtained from the Web of Science Core Collection. Results: A total of 4,392 papers were included in the bibliometric analysis. Materials Science and Nanoscience & Nanotechnology took an increasing part in the field of cancer gene therapy. Additionally, WANG W was the most productive author, while ZHANG Y ranked top in terms of citations. Harvard Medical School and Sichuan University ranked top in the active institutions. P NATL ACAD SCI USA was identified as the core journal in the field of cancer gene therapy. ‘Ovarian cancer’ was found to be the latest keyword with the strongest burst. The keyword analysis suggested that the top 3 latest clusters were labelled ‘gene delivery’, ‘drug delivery’ and ‘gene therapy’. In the reference analysis, cluster#2 labelled ‘gene delivery’ held a dominant place considering both the node volume and mean year. Conclusion: The academic attention on cancer gene therapy was growing at a dramatically high speed. Materials Science and Nanoscience & Nanotechnology might become promising impetus for the development of this field. ‘Gene delivery’ was thought to best reflect the research frontier on cancer gene therapy. The top-cited articles on gene delivery were focused on several novel non-viral vectors due to their specialty compared with viral vectors. ‘Ovarian cancer’ was likely to be the potential research direction. These findings would help medical workers conduct further investigations on cancer gene therapy.